Blikhoek - Botha, Fourie (School of Languages and Literatures, 2023)
This study examines aspects of the creative writing process and some literary statements in Joan Hambidge's novel Kladboek (2008). The possible guidance for beginner-poets present in the metafictional Kladboek is examined with reference to Fourie Botha's collection of poetry titled Blikhoek (included), which came about during work done for a Creative Writing Masters degree from the University of Cape Town